Effect of energy input on the density and shape memory effect of NiTi alloy by selective laser melting in different hatch spacing. (24th August 2022) - Qin, Sijie; Zhan, Jianbin; Lu, Yanjin; Lin, Jinxin
ABSTRACT: The number of defects is the key indicator that affects the properties of the NiTi alloy fabricated by SLM and can be adjusted by the energy density. In this study, the NiTi alloy was manufactured by varying the laser power from 50 to 95 W and matching the scanning speed of 200 to 900 mm/s at the hatch spacing of 80 and 110 μm. The results showed that the energy density for manufacturing high relative density ( 99.5%) NiTi alloy was related to the laser power and was in the range of 45 to 70 J/mm 3 . Such 'optimal energy density' gradually decreased with the laser power or hatch spacing increasing. The results of XRD and DSC revealed that when the NiTi alloy was fabricated with low laser power and small hatch spacing induced the shape memory characteristics of heat recovery prominent. Instead, when the NiTi alloy was manufactured with high laser power and large hatch spacing, it would be superelasticity.